2011
DOI: 10.1093/annonc/mdq547
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of selenium in patients with breast cancer before and after treatment of external beam radiotherapy

Abstract: Significant reduction in plasma levels of selenium is recorded in patients undergoing radiotherapy, suggesting attention to the nutritional status of this micronutrient and other antioxidant agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 20 publications
3
18
0
1
Order By: Relevance
“…Radiotherapy induces a much greater decrease of plasma Se level in patients with cancer. For example, It was noted in patients treated by radiotherapy for breast cancer that the mean serum Se level dropped from 86.4 μg/l before radiotherapy to 47.8 μg/l after it (15). In another study of 95 patients with brain metastases from non-small cell lung cancer, the mean plasma Se level decreased from 90.4 μg/l before radiotherapy to 56.3 μg/l after radiotherapy of the brain metastases (16) and this difference was statistically significant in a multivariate analysis independently of age, body mass index, smoking, alcoholism, prior chemotherapy and pathological types.…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy induces a much greater decrease of plasma Se level in patients with cancer. For example, It was noted in patients treated by radiotherapy for breast cancer that the mean serum Se level dropped from 86.4 μg/l before radiotherapy to 47.8 μg/l after it (15). In another study of 95 patients with brain metastases from non-small cell lung cancer, the mean plasma Se level decreased from 90.4 μg/l before radiotherapy to 56.3 μg/l after radiotherapy of the brain metastases (16) and this difference was statistically significant in a multivariate analysis independently of age, body mass index, smoking, alcoholism, prior chemotherapy and pathological types.…”
Section: Discussionmentioning
confidence: 99%
“…Franca et al evaluated the effects of RT on plasma Se concentration in 209 breast cancer patients and reported a significant reduction in the plasma selenium concentration (p < 0.001) for the patients undergoing RT. 7 The role of SOD in breast cancer blood cells was also investigated by Pajovic et al 25 The authors stated that alterations in the SOD activity is directly related to the initiate status of this enzyme in the conditions of high baseline level of SOD activity, RT would decrease this activity, but in conditions in which the primary activity is medium or low, the activity would be approximately constant or might even increase after the RT. As another example, in the study carried out by Kasapovic et al on breast cancer patients, RT significantly increased the activities of SOD and CAT enzymes, but there were no steady changes in GPx activity in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…The study of Franca et al is consistent with our study as they showed a significant lowered selenium levels in breast cancer patients with advanced age (>60), compared before and after the RT. 7 As we know, Se plays very important roles in a number of biological processes. On the other hand, it is a component of Gpx enzyme and alteration in glutathione peroxidase activities depended on the serum Se concentration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2010, a Brazilian prospective study showed a significant reduction in plasma levels of selenium in breast cancer patients undergoing radiotherapy, suggesting attention to the nutritional status of this micronutrient and other antioxidant agents. 5 The thoughtful radiation oncologist is thus mainly concerned with the following clinical aspects: radioprotection of normal tissues, radio-sensitizing of malignant tumor cells, protection from edematous effects, and adjuvant measures for primary and secondary cancer prevention. 6 Clinical and experimental evidence indicates that Se could address most of these issues because it functions as a radio-and chemoprotector with the ability to alleviate the side effects of tumor-specific chemotherapy or radiotherapy treatments.…”
Section: Introductionmentioning
confidence: 99%